Pengaruh Penggunaan QRIS dan Kualitas Pelayanan terhadap Loyalitas Pelanggan - Asbaruna, Latifah Wulandari (Jurnal Dimamu, 2025)
The rapid advancement of digital payment systems has encouraged businesses to adopt more efficient transaction methods, such as QRIS (Quick Response Code Indonesian Standard). Amid growing competition, service quality remains a crucial aspect in retaining customers. This study aims to analyze the extent to which QRIS usage and service quality influence customer loyalty. The research was conducted at CV Laris Barokah using a quantitative approach. Data were obtained through questionnaires distributed to consumers who had used QRIS for transactions. Respondents were selected using purposive sampling, and the data were analyzed using multiple linear regression to test both simultaneous and partial effects of the independent variables on customer loyalty. The findings indicate that QRIS usage has a positive and significant effect on customer loyalty. However, service quality emerges as a stronger and more dominant factor in shaping long-term customer relationships. These results highlight that while digital payment adoption is essential for offering convenience, the role of excellent service cannot be overlooked in fostering sustained customer loyalty. Therefore, businesses must strike a balance between digital innovation and continuous service quality improvement to ensure long-term customer commitment.